Association between heaviness of cigarette smoking and serious psychological distress is stronger in women than in men: a nationally representative cross-sectional survey in Japan - Kimiko Tomioka; Midori Shima; Keigo Saeki (BMC, 2021)
Abstract Background Higher smoking prevalence in people with serious psychological distress (SPD) is well-recognized. However, gender and age differences in the association between heaviness of cigarette smoking and SPD have not been fully investigated. Methods We used anonymized data from a nationally representative survey in Japan (33,925 men and 37,257 women). SPD was measured using the Kessler 6-item Psychological Distress Scale and defined as ≥ 13 points. Multiple logistic regression analyses stratified by gender and age-groups (20-44 years, 45-64 years, and ≥ 65 years) were used to estimate adjusted odds ratio (aOR) and 95% confidence interval (CI) for SPD. Results After adjusting for sociodemographic confounders including education, equivalent household expenditures, and employment contract, women had a significant association between heavier smoking and more frequent SPD: compared to never-smokers, aORs (95% CIs) of ex-smokers, current light smokers who smoked 1-10 cigarettes per day (CPD), current moderate smokers 11-20 CPD, and current heavy smokers ≥ 21 CPD were 1.22 (0.92-1.63), 1.52 (1.25-1.84), 1.75 (1.46-2.09), and 2.22 (1.59-3.10), respectively (P-trend < 0.001). A significant positive association among women was consistent across all age-groups. Among men, there was no association between heaviness of cigarette smoking and SPD in all age-groups, and only current heavy smokers aged 20-44 years had a significantly higher OR for SPD (aOR, 1.37 [95% CI, 1.02-1.85]) than never-smokers. Conclusions There was a positive association between heaviness of cigarette smoking and SPD only among women, but not among men. For female smokers experiencing mental disorders, there is a need not only to improve mental health services but also to improve smoking-cessation support.